Economic and social aspects of food security - Lukášková, Eva, 1977-; Pitrová, Kateřina (Tomas Bata University in Zlín, Faculty of Logistics and Crisis Management, 2018)
"The book provides expert information on food security, focusing on its economic and social aspects on a global and national scale. It reflects the current situation of food self-sufficiency, food safety, economic accessibility within the EU and the Czech Republic. The book is intended for experts interested in food security issues from the point of view of its theoretical definition and practical impacts within the economic system of the Czech Republic. The book can also be used by people from the general public who are interested in obtaining expert information on the current issue." -- Resumé vydavatele
Keywords: potravinová bezpečnost; potravinová bezpečnost -- ekonomické aspekty; potravinová bezpečnost -- sociální aspekty; food security; food security -- economic aspects; food security -- social aspects; monografie; elektronické knihy; monographs; electronic books